A Study on the Prevalence of Premenstrual Dysphoric Disorder in Medical Students (Academia Journal of Medicine, 2024)
Background: Premenstrual dysphoric disorder is a common yet underdiagnosed mental health problem among women of reproductive age group with a significant potential to perturb the social, occupational, academic and interpersonal milieu of the suffering women. The aim of the study is to determine the frequency and severity of the premenstrual dysphoric disorder (PMDD) in medical college students. The premenstrual dysphoric disorder is a common yet underdiagnosed mental health problem among women of reproductive age group with a significant potential to perturb the social, occupational, academic and interpersonal milieu of the suffering women. Subjects and Methods: Premenstrual dysphoric disorder was diagnosed based on Penn’s daily symptom rating scale (self-administered for 2 months) and an interview-based on diagnostic and statistical manual -5 diagnostic criteria for the premenstrual dysphoric disorder. Results: Overall 180 subjects were studied. The prevalence of premenstrual dysphoric disorder was wound to be 11.11 % (n= 20). The most common symptoms found were fatigue irritability, mood swings and A significant correlation between the severity of premenstrual and menstrual difficulties was found with PMDD. Conclusion: The current study highlights the need for clinicians to assess for premenstrual dysphoric disorder in females visiting the hospital with premenstrual and menstrual complaints.
Keywords: Premenstrual Dysphoric Disorder; Menstrual Complaints